2010
DOI: 10.2478/s11756-010-0080-0
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype, meiotic behavior and pollen features of Senna occidentalis

Abstract: Meiotic behavior, pollen morphology, interphasic nucleus pattern and karyotype description for Senna occidentalis (Caesalpinioideae -Fabaceae) are presented. The species had non-reticulate interphasic nucleus and homogeneous chromosome condensing with minute distal late-condensing portions in prometaphase. In mitotic metaphase, chromosome number was 2n = 28 (9 m + 5 sm), with secondary constriction in one chromosome pair. Detection of four nucleoli indicated existence of two chromosome pairs bearing Nucleolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
3
3
0
Order By: Relevance
“…In case of exine ornamentation, mainly rugulate and granulate type ornamentation was observed across the species. Similar result in case of S. occidentalis had been reported by others (16) . However, in S. occidentalis rugulate-fossulate arrangement was found (Fig.…”
Section: 2e-f 2h-i 2k-l and 2n-o)supporting
confidence: 91%
See 1 more Smart Citation
“…In case of exine ornamentation, mainly rugulate and granulate type ornamentation was observed across the species. Similar result in case of S. occidentalis had been reported by others (16) . However, in S. occidentalis rugulate-fossulate arrangement was found (Fig.…”
Section: 2e-f 2h-i 2k-l and 2n-o)supporting
confidence: 91%
“…All the species showed tricolporate type pollen with difference in the measurements of colpal length and equatorial axis length (Table 2) parallel to other research findings (14)(15)(16) . In case of exine ornamentation, mainly rugulate and granulate type ornamentation was observed across the species.…”
Section: 2e-f 2h-i 2k-l and 2n-o)supporting
confidence: 87%
“…Pollen morphology helps to solve several taxonomic troubles at the level of family, genus, or species (Carlo & Paula, 2004;Joujeh, Zaid, & Mona, 2019) which provides an example in which anatomy and palynology could be used to resolve a taxonomic dilemma (Figure 3). Exine sculpturing and permanent characters made the pollen grains significantly identifiable features by which ancestral genera and even species can recognize (Ferreira, Torres, de Sousa, & dos Santos, 2010;Maw et al, 2020) is similar to previous findings of Dawar, Qaiser, and Perveen (2002) who used type of tectum for identification and also observed striate sculpturing for B. variegata which confirms the present work. Sexine was thicker than nexine in all nine studied species (Figures 4, 5, and 6).…”
Section: Introductionsupporting
confidence: 92%
“…Exine sculpturing and permanent characters made the pollen grains significantly identifiable features by which ancestral genera and even species can recognize (Ferreira, Torres, de Sousa, & dos Santos, 2010; Maw et al, 2020). Four types of surface ornamentation, psilate, granulate, clavate, and perforate, were recorded.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of intensive pharmacological studies, few studies have been done about biological aspects of the species. Considering the medicinal importance of Plectranthus barbatus and a large number of synonyms reported, basic information such as karyotypic traits are very important, helping the correct plant identification and also the production of commercial varieties in breeding programs ( Sousa et al 2009 , Ferreira et al 2010 , Sousa et al 2010 , Pierre et al 2011 , Sousa et al 2012 , Sousa et al 2013 , Reis et al 2014 , Viccini et al 2014 ). Regarding cytogenetic studies, only the chromosome number and meiosis behavior were reported so far ( De Wet 1958 , Morton 1962 ).…”
Section: Introductionmentioning
confidence: 99%